Learning from Youth Voice: Student Reflections on Common Approaches in Youth Sports - Julie McCleery; Chloe Stanton; Beatrice Wurfel; Sarah Smith; Irina Tereschenko (Youth)
In youth sports, young people are often subjected to approaches and coach behaviors misaligned with their physical and psychological development, including early specialization and the use of physical activity as punishment. Little research investigates these practices from the perspective of youth. This study used novel qualitative approaches to explore student reactions to these practices. Over four years, students who took an Introduction to Psychology class at one private high school in a West Coast city received a presentation about topics at the intersection of sports and psychology and submitted their reflections. A student-led research team analyzed the 332 reflections. The findings show that the information in the Long-Term Athlete Development framework was dissonant with student experiences in the U.S. youth sports system. Many had negative experiences with physical activity as punishment. Providing youth with information about developmentally appropriate practices in sports can help them advocate for change that will protect them and others from harm.